2020
DOI: 10.1089/3dp.2020.0101
|View full text |Cite
|
Sign up to set email alerts
|

Considerations and Cautions for Three-Dimensional-Printed Personal Protective Equipment in the COVID-19 Crisis

Abstract: The recent decline in available personal protective equipment (PPE) due to the novel coronavirus (COVID-19) pandemic has given rise to a host of three-dimensional (3D) printed prototypes for facemask and respirator units. Many of these models have been made open access and publicly available for printing and use, and have been promoted by various media outlets. Although these desktop 3D printing measures have provided a possible venue for success in providing homemade and cost-effective PPE to health care work… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(49 citation statements)
references
References 5 publications
1
46
0
2
Order By: Relevance
“…Likewise, different 3D printers have different thermoplastic filaments that vary in composition and properties. 3D-printed PPE can pose a possible threat if the filament is prone to retaining moisture in the environment, which can inadvertently transmit virus particles [63]. (b) FDA-approved surgical masks are to be used by healthcare workers in the absence of N95 respirators; (c) The regular method for tying surgical masks compared to the newly proposed method that can secure the side openings of surgical masks; (d) A surgical mask design modified with filter performance rating (FPR) 9-10 air-conditioning filters; (e) The Stanford full-face, snorkel-inspired Pneumask.…”
Section: Masks and Shieldsmentioning
confidence: 99%
“…Likewise, different 3D printers have different thermoplastic filaments that vary in composition and properties. 3D-printed PPE can pose a possible threat if the filament is prone to retaining moisture in the environment, which can inadvertently transmit virus particles [63]. (b) FDA-approved surgical masks are to be used by healthcare workers in the absence of N95 respirators; (c) The regular method for tying surgical masks compared to the newly proposed method that can secure the side openings of surgical masks; (d) A surgical mask design modified with filter performance rating (FPR) 9-10 air-conditioning filters; (e) The Stanford full-face, snorkel-inspired Pneumask.…”
Section: Masks and Shieldsmentioning
confidence: 99%
“…Similar risks and concerns were also reviewed and reported by Clifton et al . (2020)[ 30 ]. The authors reported that during this pandemic, the open distribution and propagation of PPE prototypes happened before validation and hypothesis formulation (in the context of both engineering and biological considerations) that emphasized on the fundamentally important factors for prototype testing, such as number needed to treat and reduce harm for patients, and the approval of health service authorities had not been considered.…”
Section: Resultsmentioning
confidence: 99%
“…Hence, it was possible to highlight the need for universal standardization for PPE, such as medical face shield products. True innovation can prevail over brief notoriety and avoid unintentional harm from good intentions led by poor science[ 30 ]. This study provided an original design which was developed based on scientific principles of advanced engineering design and AM methods, with the product being convenient for single-use (means of economic base) and sterilization (with limited cycles) in case of reuse in a risk-based environment such as COVID-19 (+) with close HW-patient interaction.…”
Section: Resultsmentioning
confidence: 99%
“…The FDM is the most commonly used 3D printing method using thermoplastics materials, with ease of handling, rapid processing, simplicity, and cost-e ciency [25]. The nal cost is reduced due to machine and material low cost, but the process shows some limitations [47], as laments such as PLA and ABS vary in material composition, porosity, and environmental stability. Although no mechanical tests were performed with the 3D printed face shields in this study, it is known that mechanical properties such as tensile strength, Young's modulus, elongation at break, and impact strength are lower in an object that is manufactured under FDM process compared with the ones under the IM process [48].…”
Section: Qualitative Comparison Of Fdm and Im Processes To Produce Famentioning
confidence: 99%